Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1136/bmjopen-2019-033997
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of titanium mesh cranioplasty and polyetheretherketone cranioplasty: protocol for a multicentre, assessor-blinded, randomised controlled trial

Abstract: IntroductionCranioplasty is a common surgery in neurosurgery department. However, restoring the integrity of skull brings many challenges to surgeons, and the selection of ideal implant materials is throughout the history of cranioplasty. Although titanium mesh was still preferred by many neurosurgeons in cranial reconstruction, the new polyetheretherketone (PEEK) material, for example, is gaining popularity for craniofacial reconstruction today. There remain limited data that compare the outcome of PEEK crani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 24 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…29,30 Finally, the implant material is characterized by higher biocompatibility and osseointegration as well as bonelike elasticity and strength, and it is also associated with lower susceptibility to infection. [31][32][33] Although artifacts due to the metal nature of the implant made it difficult to evaluate the postoperative MRI images, the use of different sequences on different planes and the comparison of pre-and postoperative images allowed us to rule out a residual or new compression of the cerebellum in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Finally, the implant material is characterized by higher biocompatibility and osseointegration as well as bonelike elasticity and strength, and it is also associated with lower susceptibility to infection. [31][32][33] Although artifacts due to the metal nature of the implant made it difficult to evaluate the postoperative MRI images, the use of different sequences on different planes and the comparison of pre-and postoperative images allowed us to rule out a residual or new compression of the cerebellum in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-unique implants are a recent addition to available choices for cranioplasties [ 11 ]. These implants are created using computer-aided design and manufacture (CAD/CAM) based on patient's CT scan data and subsequently are 3D printed [ 5 , 9 , 11 , 12 ]. Synthes, Biomet, KLS Martin, OsteoMed, and OssDsign (Sweden) all report decreased operating times, better fits, and increased patient satisfaction with the use of PSI, but many of the MAUDE events report detailed intraoperative delays, in which the surgeon had to adjust the implant to achieve a better match to the patient’s defect [ 17 - 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even with this wide variety of options of inserts for cranioplasty surgeons, there has been little research performed describing complications of artificial cranioplasty plates after surgery [3,[7][8][9]. Therefore, this study aimed to provide a further assessment of post-operative complications of artificial cranioplasty plates after surgery by characterizing complications reported to a large federal database.…”
Section: Introductionmentioning
confidence: 99%
“…An empiric antimicrobial treatment covering Gram-positive and Gram-negative germs was started. The appropriate response to therapy was ascertained and followed over time, monitoring systemic and local clinical signs [15]. Walcott et al [14] also reported that patient age, location of cranioplasty, presence of an intracranial device, bone flap preservation method and cranioplasty material were not predictive of the development of cranioplasty infection.…”
Section: Discussionmentioning
confidence: 99%